Optimization of Optical Distribution Point Device Placement on Fiber Optic Cable Networks to Homes - Wahyudiono, Pratiwi Hendro; Indrapriyatna, Ahmad Syafruddin (International Journal of Recent Technology and Applied Science (IJORTAS), 2024)
Competition in telecommunications technology places demands on companies to always innovate to release the latest services. Currently, the issue of optical distribution point (ODP) infrastructure has become important in fiber to the home (FTTH) network access. This research aims to optimize the placement path for ODP devices on PT BCV’s FTTH network using a traveling salesman problem (TSP) scheme with a hybrid genetic algorithm approach, testing is carried out using Matlab software. From the results obtained in this study, it was concluded that the hybrid genetic algorithm parameters for a population size of 100 with a number of iterations of 2000 by comparing the combination of cross probability parameters of (0.25), (0.5), and (1) and mutation probability of (0.050), (0.025) and (0.005) produces the best fitness value in the combination of Pcrossover = 0.25 and Pmutation = 0.005 and the worst fitness value in the combination of Pcrossover = 1.00 and Pmutation = 0.025. Therefore, researchers recommend a combination of genetic algorithm hybrid parameters with a combination of Pcrossover = 0.25 and Pmutation = 0.005 with a population of 100 and with a number of iterations of 2000.